2021
DOI: 10.1080/17408989.2021.1953459
|View full text |Cite
|
Sign up to set email alerts
|

The influence of online physical activity interventions on children and young people’s engagement with physical activity: a systematic review

Abstract: Background: Most children and young people (CYP) worldwide are classified as inactive because they fail to meet the World Health Organisation recommendations for physical activity. Online interventions that use devices like exergames, smartphones, social media, and wearables have the potential to improve physical activity engagement because of their extensive reach and opportunities for learning and use across contexts. Purpose: The objectives of this systematic review were to update the evidence-base on onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 58 publications
0
57
0
1
Order By: Relevance
“…Furthermore, children and adolescents are important target populations for digital interventions that focus on physical activity promotion because the use of digital technologies contributes to sedentary behavior, especially in early childhood [ 75 ]. Therefore, future research should consider potential benefits but also harms of digital technologies and thus, evaluate if digital interventions promote or hinder physical activity in children and adolescents [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children and adolescents are important target populations for digital interventions that focus on physical activity promotion because the use of digital technologies contributes to sedentary behavior, especially in early childhood [ 75 ]. Therefore, future research should consider potential benefits but also harms of digital technologies and thus, evaluate if digital interventions promote or hinder physical activity in children and adolescents [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from systematic reviews have demonstrated the effectiveness of gamification at achieving positive outcomes within a range of contexts including health and well-being and education (Dicheva et al, 2015; Johnson et al, 2016; Manzano-León et al, 2021). Additionally, in a systematic review of online PA interventions with young people, gamification was found to be one of the main mechanisms to elicit positive changes in young people's behaviours (Goodyear et al, 2021). More specifically, recent studies have reported positive motivational outcomes to be associated with the use of gamification in PE across multiple age ranges (Fernandez-Rio et al, 2020; Ferriz-Valero et al, 2020).…”
Section: Blended-gamified Pementioning
confidence: 99%
“…To alleviate the detrimental health consequences of negative emotions (e.g., sleep problems), relaxation training and cognitive behavioral therapy can be recommended to improve sleep quality ( Zhou et al, 2020 ). Furthermore, offering physical training interventions at a safe distance (e.g., outdoor or via an online class) can be implemented as there is evidence that such interventions improve social aspects, sleep quality, and reduce the time spent on sedentary behavior ( Goodyear et al, 2021 ; Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%